NEW APPROACHES IN RESEARCH OF GREGORIAN CHANT: ETHNOMUSICOLOGICAL ASPECT (Mūzikas akadēmijas raksti, 2024)
The main issue of this paper is questions concerning the manuscript Missale Rigense (the Missal of Riga), dating back to the 14th century. The primary issue I am going to focus on is finding an answer to the question if the musical material of the above manuscript comprises any particular local music tradition at all, owing to the fact that this aspect, being directly linked with such issues as history and identity, in the music history of medieval Riga has never been investigated. This issue immediately entails the problem of choosing the most appropriate methodology and approaches towards investigating the relevant problem. This undoubtedly poses another question, concerning the notion of globality and locality in music.